Alveolar distraction osteogenesis: Archwise appliance and technique - (:unkn) unknown (Springer International Publishing, 2015)
This book describes a new method of alveolar distraction osteogenesis that offers important advantages and can be used for the treatment of various orthopedic abnormalities and congenital malformations. Detailed guidance is provided on selection of patients suitable for alveolar distraction, including those with cleft lip and palate, skeletal class II malocclusions and cystic lesions involving the alveolus. All aspects of treatment using the ArchWise distraction appliance are then covered, including technical preparation, surgical set-up and osteotomies, docking site surgery, orthodontic finishing, implant placement and prosthetic restorations. Relevant information is also included on the principles of distraction osteogenesis and bone histology and quality after the procedure. The book concludes with helpful case presentations covering different scenarios in which ArchWise distraction of alveolar bone is appropriate. © Springer International Publishing Switzerland 2015.